Narrative Structures and Methodological Principles in Boyer and Merzbach’s Historiography for Mathematics Education - Kintoko Kintoko; Deny Hadi Siswanto; Nanang Khuzaini (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This study aims to analyze the narrative structure, periodization, and methodological principles in A History of Mathematics by Carl B. Boyer and Uta C. Merzbach (third edition, 2011) as a historiographical model in mathematics education. The research employs a descriptive qualitative approach using the content analysis method. Data were collected through an in-depth reading of all chapters of the book and analyzed based on two main dimensions: internal history (the development of concepts and mathematical rigor) and external history (the social, cultural, and economic influences on the emergence of mathematical ideas). The findings reveal that Boyer and Merzbach construct the historical narrative of mathematics both chronologically and thematically, tracing its evolution from ancient to modern times while emphasizing the continuity of mathematical ideas across civilizations. Merzbach’s approach, which integrates linguistic, social, and economic contexts, demonstrates that the development of mathematics is the result of an interaction between abstract ideas and human practical needs. Furthermore, the principle of “extension without correction” indicates that each new mathematical theory does not negate earlier ones but rather expands and enriches the existing scientific framework. The study concludes that A History of Mathematics possesses significant pedagogical value and is highly relevant as a learning resource for the history of mathematics, as it cultivates a philosophical and historical understanding of mathematics as both a cultural product and an ongoing intellectual process